Motivational reminder model for medication adherence : an internalization approach - Zhang, Yaming (Nanyang Technological University, 2022)
Resolving the issue of medication non-adherence is a top priority in order to tackle chronic diseases effectively. State-of-the-art solutions for patients typically focus on medication reminders, which did not address the issue for those who intentionally do not adhere to their medications. At the heart of medication adherence is motivation; self-initiated healthy behaviours tend to generate long-lasting healthy effects alongside desired satisfaction. The challenge therefore lies in motivating individuals to adhere to their medication schedules.